A phase III, randomized, controlled noninferiority trial to study the efficacy and safety of imipenem/cilastatin/relebactam (IMI/REL) vs piperacillin/tazobactam (PIP/TAZ) in patients with hospital-acquired bacterial pneumonia (HABP) or ventilator-associated bacterial pneumonia (VABP) - Junjie Li; Feng Wei; Peng Xiang; Zhengang Tang; Lianshu Ding; Luke Francis Chen; Maria Losada; Zlatka Iamboliyska; Fang Sun; Mingfen Zhu; Xiaodan Guo; Xiaoling Du; et al. (International Journal of Infectious Diseases)
Objectives: Imipenem/cilastatin/relebactam (IMI/REL) is a β-lactam/β-lactamase inhibitor combination effective against gram-negative pathogens. Efficacy and safety of IMI/REL were studied in critically ill adults with hospital-acquired bacterial pneumonia (HABP) or ventilator-associated bacterial pneumonia (VABP). Methods: In this phase III, double-blind, multinational, randomized trial (NCT03583333), adults with HABP/VABP were randomized 1:1 to receive intravenous IMI/REL (500 mg/250 mg) or piperacillin/tazobactam (PIP/TAZ; 4000 mg/500 mg) every 6 h for 7-14 days. The primary endpoint was 28-day all-cause mortality (ACM). Secondary endpoints were clinical response (CR), microbiological response (MR), and adverse event (AE) incidence. Results: In the modified intention-to-treat population (N = 270 [IMI/REL: n = 134; PIP/TAZ: n = 136]), demographics and baseline characteristics were comparable between treatment groups. Most patients were from China. IMI/REL was noninferior to PIP/TAZ for 28-day ACM (11.2% vs 5.9%; adjusted difference [95% confidence interval]: 5.2% [−1.5 to 12.4]). Secondary outcomes were comparable between treatment groups, including favorable CR and MR. AEs resulting in death were generally consistent with pre-existing or underlying illness. Conclusions: IMI/REL met noninferiority criteria vs PIP/TAZ for 28-day ACM, and safety profiles were comparable. This trial could support the use of IMI/REL to treat adults with HABP/VABP, including regional use in China.